2018
DOI: 10.1039/c7cp08436f
|View full text |Cite
|
Sign up to set email alerts
|

Photoreaction of BlrP1: the role of a nonlinear photo-intensity sensor

Abstract: Blue-light-regulated phosphodiesterase 1 (BlrP1) is a blue light sensor protein that controls the hydrolysis of cyclic dimeric guanosine monophosphate, which regulates cellular motility, virulence, and formation of biofilms. In this report, the photoreaction dynamics of BlrP1 and its blue light sensor using a flavin adenine dinucleotide (BLUF) domain were investigated by the time-resolved transient grating method. Only a minor conformational change of the BlrP1-BLUF domain was observed. In contrast, a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 34 publications
(53 reference statements)
2
36
0
Order By: Relevance
“…The procedure for expression and purification of the blrP1 gene has been described previously [7]. Briefly, the blrP1 gene (N559_2724) was cloned into the pET expression vector pET His6 MBP TEV LIC (2 M‐T), which was a gift from Scott Gradia (Addgene plasmid #29708).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure for expression and purification of the blrP1 gene has been described previously [7]. Briefly, the blrP1 gene (N559_2724) was cloned into the pET expression vector pET His6 MBP TEV LIC (2 M‐T), which was a gift from Scott Gradia (Addgene plasmid #29708).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that this change allosterically regulates the enzymatic activity through the interaction at the dimeric interface [5,6]. Recently, the reaction scheme and kinetics of BlrP1 have been identified by the transient grating (TG) method [7]. The conformational change was detected as a significant decrease in its diffusion coefficient (D), which was mainly attributed to the quaternary structural change in the dimer via a diffusion-sensitive conformational change (DSCC).…”
mentioning
confidence: 99%
“…Photon absorption induces structural changes in the BLUF domain that are propagated to an adjacent output domain to regulate it allosterically. A detailed mechanism of sensory perception by the BLUF domain-containing c-di-GMP-specific PDE BlrP1 ( 26 , 46 , 93 97 ) is discussed in the section on photosensing.…”
Section: Modular Sensory and Receiver Domains Found In Dgcs And C-di-...mentioning
confidence: 99%
“…Previous transient grating (TG) measurements have revealed that the two proteins (BlrP1 and YcgF) also show millisecond conformational changes, despite the absence of Trp and the τ2-phase. 37,38 Hence, in these cases, the slow conformational change may be caused by the τ1-phase through different signaling pathways. NMR measurements of BlrP1 indicate that the blue light induces conformational changes in α3-and α4-helices extending from the Cterminus of the BLUF domain.…”
Section: Origin Of τ 2 -Phasementioning
confidence: 99%
“…Previously, the global conformational changes of many BLUF proteins have been detected by the TG technique. 37,38,43,44,45 For example, the time constants of the conformation changes far from the chromophore for PapB, BlrP1, SyPixD, and TePixD have been reported to be 24 ms, 45 21 ms, 38 350 ms, 46 and 4 ms, 44 , respectively. It is interesting to note that the time constant of PapB (24 ms) are relatively close to those observed from the slow absorption change (τ2 = 12 ms).…”
Section: Signaling Pathway Of Bluf Proteinsmentioning
confidence: 99%